The Safe Online Together Project: A participatory approach to resolving inter-generational technology conflict in families. Issue 2 (3rd April 2022) - Page Jeffery, Catherine; Atkinson, Susan; McCallum, Kerry
ABSTRACT: Digital media technologies are a ubiquitous feature of contemporary family life. However, their presence has reconfigured traditional family power relations and, in some cases, subverted family hierarchies of expertise, resulting in conflict between parents and children. This article discusses the methodological approach of the Safe Online Together project, an action research project designed to reduce media-related family conflict by promoting intergenerational understanding and knowledge sharing between parents and children in a non-hierarchical space. In a departure from contemporary 'deficit' approaches that can treat young people as dangerous risk-takers in the online environment, the project adopts and encourages more democratic methods and provides young people with the opportunity to share the ways they navigate online risks with their families through a series of family workshops. Early findings provide a strong justification for the project's approach, and indicate that the family workshops in particular can help families navigate the online world together.